Revue de droit d'Assas - Touzain, Antoine (Université Paris 2, 2017)

Entrepreneurship in Africa - Akinyoade, Akinyinka; Dietz, Ton; Uche, Chibuike (Brill, 2017)
Historically, entrepreneurs have always played a central role in the development of nation states. Aside from rentier states, which depend extensively on the availability of mineral resource rents, most economically prosperous nations in the world have strong, innovative and competitive business enterprises and entrepreneurs as the bedrock of their economic development and prosperity. It was arguably because of the above historical fact that the World Bank in 1989 declared that entrepreneurs will play a central role in transforming African economies. Chapters in this book contribute to our understanding of the theory, structure and practice of entrepreneurship in diverse African countries. Case studies examined include: African multinational banks and businesses, female entrepreneurs, culture and entrepreneurship, finance and entrepreneurship and SMEs.
Télécharger le PDF : https://brill.com/downloadpdf/display/title/33333.pdf
Keywords: African Studies; Economic History; Economics & Political Science; History; Social Sciences; Sociology & Anthropology

El derecho aéreo entre lo público y lo privado : aeropuertos, acceso al mercado, drones y responsabilidad - Contreras de la Rosa, Isabel; Guerrero Lebrón, María Jesús; Peinado Gracia, Juan Ignacio; Villanueva Turnes, Alejandro; Sales Pallarés, Lorena; Rivas Castillo, María Isabel; Casal Freiría, Armando Víctor; Uriarte Ricote, Maite; Sánchez Bartolomé, José Miguel; Vázquez Ruano, Trinidad; Buggea, Alessia; Navarro Peral, Manuela; et al. (Universidad Internacional de Andalucía, 2017)
El carácter multidisciplinar del derecho aéreo ha sido una de las razones por las que aún son escasos los estudios académicos sobre los diversos aspectos jurídicos que se entrecruzan en el sector. No obstante, ese ha sido precisamente el enfoque que han querido darle los directores a esta obra, huyendo de encorsetamientos académicos que impedirían un tratamiento global de los problemas jurídicos que se plantean en el sector aeronáutico. Atentos, pues, a los últimos avances de la realidad, se ha querido ofrecer un elenco de trabajos sobre temas significativos y de máxima actualidad que tienen en común su incidencia en el desarrollo de una actividad económica de alcance internacional, esencial en nuestro país, y que supone, igualmente, un pilar básico de la región. Y todo ello desde la Universidad, pero en contacto directo con el entorno empresarial y profesional, pues esa simbiosis es la única que puede hacer de una obra jurídica como ésta un estudio verdaderamente útil.
Accepted: 2017-09-28T07:27:52Z

The Independence and Impartiality of ICSID Arbitrators: Current Case Law, Alternative Approaches, and Improvement Suggestions - Cleis, Maria Nicole (Brill, 2017)
In The Independence and Impartiality of ICSID Arbitrators, Maria Nicole Cleis examines the standard of independence required under the ICSID Convention, as evidenced in existing disqualification decisions, and makes novel suggestions for reforms to ensure unbiased decision-making. Readership: All interested in International Investment Law and investor-State arbitration in particular. Readership includes academics, lawyers and arbitrators involved in investment-related disputes (including in-house counsel), treaty negotiators and NGOs.
Accepted: 2020-05-15T17:36:32Z
Keywords: Arbitrage; Arbitragem; Arbitration; Civil procedure; International Arbitration; International disputes; International law

Guide du secrétariat de la CNUDCI sur la Convention pour la reconnaissance et l’exécution des sentences arbitrales étrangères (New York, 1958) - Commission des Nations Unies pour le Droit Commercial International (Nations Unies, 2017)

Textos internacionales sobre garantías mobiliarias: reflexión y análisis - Delgado, Carmen Jerez (Agencia Estatal Boletín Oficial del Estado, 2017)
Los Textos internacionales sobre garantías mobiliarias constituyen, actualmente, un reto para nuestro Derecho interno. No es posible omitir la referencia a ellos y es necesario abrir una reflexión sobre las ventajas de la armonización jurídica, a la vista de la emergente hegemonía del sencillo y flexible modelo anglosajón plasmado en el artículo 9 del Uniform Commercial Code. Este es precisamente el objeto del libro que el lector tiene en sus manos. En un mercado globalizado, la actualidad de los referidos textos internacionales hace ineludible la tarea de repensar el derecho interno en materia de garantías mobiliarias. Con mayor razón cuando forman parte de nuestro Derecho interno. Así, entre los textos de Derecho uniforme, España ha ratificado el Convenio relativo a las Garantías internacionales sobre elementos de equipo móvil, del Instituto Internacional para la Unificación del Derecho privado (UNIDROIT, Ciudad del Cabo, 2001), y uno de sus correspondientes protocolos, relativo a aeronaves. En el ámbito europeo, España ha traspuesto la Directiva 2002/47/CE, y puede tener como referencia -en el contexto del Soft Law- el Libro IX del DCFR. En todo caso, no puede resultarnos ajena la proliferación de Leyes Modelo en la materia, emanadas de diversos organismos internacionales, y su impacto en otros países (así, la Ley Modelo sobre Garantías mobiliarias de la Comisión de las Naciones Unidas para el Derecho Mercantil Internacional, CNUDMI, 2016; La Ley Modelo Interamericana sobre Garantías Mobiliarias de la Organización de Estados Americanos, OEA, 2002; La Ley Uniforme de la Organización para la Armonización de la Legislación empresarial en África, OHADA, 1997; o la Ley Modelo sobre Operaciones garantizadas del Banco Europeo de Reconstrucción y Desarrollo, BERD, 1994). El propósito de este libro es presentar las líneas que encontramos en los más destacados textos de Derecho uniforme, y facilitar su comprensión, contagiar el interés por asomarse a ellos.

Repenser la légitimité de l'État africain à l'ère de la gouvernance partagée - Gazibo, Mamoudou; Moumouni, Charles (Presses de l'Université du Québec, 2017)
Le contexte dans lequel l'État africain évolue a profondément changé, notamment depuis l'ouverture démocratique des années 1990. L'environnement institutionnel est désormais marqué par une prolifération d'acteurs nouveaux, disputant le monopole de l'action publique. Cet ouvrage aborde cette nouvelle donne en explorant sur les plans local, national et international, son effet sur la substance et la légitimité de l'État africain.

Doing Business dans les Etats membres de l’OHADA : Comparaison des réglementations s'appliquant aux entreprises locales dans 17 Etats membres et à travers le monde - Groupe des Indicateurs Globaux (Banque mondiale, 2017)

East African Community Law: Institutional, Substantive and Comparative EU Aspects - Ugirashebuja, Emmanuel; Ruhangisa, John; Ottervanger, Tom; Cuyvers, Armin (Brill, 2017)
East African Community Law provides a comprehensive and open-access text book on EAC law. Written by leading experts, including the president of the EACJ, national judges, academics and practitioners, it provides the most complete overview to date of this increasingly important field. Uniquely, the book also provides a systematic comparison with EU law. EU companion chapters provide concise overviews of EU law and its development, offering valuable inspiration for the application and further development of EAC law. The book has been written for all practitioners, judges, civil servants, academics and students faced with questions of EAC law. It discusses institutional, substantive and jurisdictional issues, including the nature of EAC law, free movement and competition law as well as the reception of EAC law in Partner States.
Keywords: Comparative law